Making Space: Reading the Truth and Reconciliation Commission of Canada's Report in and Beyond the Classroom through Practice-Based Research - Doonan, Natalie; Bouvelle, Sara; Issa, Gaëlle; Villarreal Herrera, Mariana (Performance Matters, 2023)
In a graduate-level Digital Storytelling course in the Department of Communication at the Université de Montréal, the first project I assign is called a “Collective Experimental Story.” The intention of this project is to introduce students to collaborative storytelling and to explore a platform that enables participatory forms of presentation and co-creation. I enter into this experimental process with students. In Fall 2021, I proposed that the project respond to the Truth and Reconciliation Reading Challenge. From 2008 to 2015, Canada’s Truth and Reconciliation Commission produced a report documenting the history and ongoing impacts of the country’s residential school system on First Nations. This report includes 94 Calls to Action, including a call for teachers at all levels to address these histories and their effects in the classroom. Students in my course were excited by this proposal. Over the first seven weeks of the course, we read the report, defined the objective and approach of our project, conducted research and development to identify a suitable platform, and divided tasks. We used Gather Town—an online meeting platform that boasts an old-school pixelated video game interface—to stage a live event. The goal was to share what we had learned and to open space for dialogue. Participants circulated as avatars in our simulated spaces. In this article, four of us who were involved in the project describe our practice-based research process.